1983
DOI: 10.1104/pp.73.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase-Deficient Mutant of Chlamydomonas reinhardii Requires Elevated Carbon Dioxide Concentration for Photoautotrophic Growth

Abstract: A mendelian mutant of the unicellular green alp Chlamydomonas reinhardii has been isolated which is deficient in carbonic anhydrase (EC 4.2.1.1) activity. This mutant strain, designated ca-1-12-1C (gene locus ca-i), was selected on the basis of a high C02 requirement for photoautotrophic growth. Photosynthesis by the mutant at atmospheric C02 concentration was very much reduced compared to wild type and, unlike wild type, was strongly inhibited by 02. In contrast to a CO2 compensation concentration of near zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
164
5
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(183 citation statements)
references
References 21 publications
13
164
5
1
Order By: Relevance
“…In addition, these growth characteristics indicated that CIA-S may have a defect in the inorganic carbon accumulation system, as its phenotype is very similar to previously described strains (18,23,24). This hypothesis was supported …”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…In addition, these growth characteristics indicated that CIA-S may have a defect in the inorganic carbon accumulation system, as its phenotype is very similar to previously described strains (18,23,24). This hypothesis was supported …”
Section: Resultssupporting
confidence: 74%
“…If these strains are placed on low levels of C02, they either cannot grow, or grow at slower than normal rates. Some of these strains are unable to accumulate C1 (24), while others accumulate Ci to levels higher than wild-type cells (23), but are unable to use this accumulated C1 efficiently. All of the previously characterized C. reinhardtii mutants were capable of inducing the synthesis of the periplasmic carbonic anhydrase (18,26) as indicated by enzyme assay or by detection with antibodies raised against the periplasmic carbonic anhydrase.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of extracellular CA located 1983). The role of CA appears to be linked to a COj-outside the plasma membrane in the periplasmic concentrating mechanism (CCM) (Badger, Kaplan space or attached to the cell wall has been reported & Berry, 1980;Spalding, Spreitzer & Ogren, 1983; for marine microalgae (Dionisio-Sese & Miyachi, 1992) iticludmg some phytoplankton species (Burns * To whom correspondence should be addressed.…”
mentioning
confidence: 99%